Risk factors for HIV infection among female sex workers in Bangui, Central African Republic - Longo, Jean De Dieu (PLoS One, 2017)
OBJECTIVE: The aims of the study were i) to categorize female sex workers (FSW) according to socio-anthropologic criteria in Bangui; ii) to examine the association between a selection of demographic and risk variables with the different categories of female sex work as outcome, and iii) to investigate factors associated with HIV status. METHODS: A cross-sectional questionnaire survey was conducted to describe the spectrum of commercial sex work in Bangui among 345 sexually active women. After collection of social and behavioral characteristics, each woman received a physical examination and a blood sample was taken for biological analyses, including HIV testing. The relationships between sociodemographic characteristics, behavioral variables involved in high risk for HIV as well as biological results were investigated by bivariate analysis in relationship with FSW categories as main outcomes, and by bivariate analysis followed by multivariate logistic regression analysis in relationship with HIV as the main outcome. The strength of statistical associations was measured by crude and adjusted Odds ratios (OR) and their 95% confidence intervals. RESULTS: The typology of FSW comprised six different categories. Two groups were the “official” professional FSW primarily classified according to their locations of work [i) “kata“(18.55%) representing women working in poor neighborhoods of Bangui; ii) “pupulenge” (13.91%) working in hotels and night clubs to seek white men]. Four groups were “clandestine” nonprofessional FSW classified according to their reported main activity [i) “market and street vendors” (20.86%); ii) “schoolgirls or students” (19.13%) involved in occasional transactional sex (during holidays); iii) “housewives or unemployed women” (15.65%); iv) “civil servants” (11.88%) working as soldiers or in the public sector]. The overall prevalence of HIV-1 was 19.12% (66/345). HIV varied according to FSW categories. Thus, among professional FSW, the HIV prevalence was 6-fold higher in "kata" than "pupulenge" (39.13% versus 6.30%; P = 0.001). Among nonprofessional FSW, the "vendors" showed the highest HIV prevalence (31.91%), which was higher than in "students" (6.10%; P = 0.001), "civil servants" (9.83%; P = 0.005), and "housewives" (13.00%; P = 0.01). In bivariate analysis, the following variables showed statistically significant association with risk for HIV infection: nationality; age of first sexual intercourse; self-assessment of HIV risk; knowledge of HIV status; anal sex practice with last clients; irregular condom use in last week; consumption of alcohol; other psycho-active substances; past history of STIs; HBs Ag; HSV-2 and bacterial vaginosis. However, the variable “sex workers categories” dichotomized into professional versus nonprofessional FSW was no longer associated with HIV. In multivariate logistical regression analysis, HIV infection was strongly associated with nationality (15.65% versus 3.77%) [adjusted OR (aOR) 3.39: 95% CI:1.25–9.16, P<0.05]; age of first sexual intercourse (21.10% versus 14.00%) (aOR 2.13: 95% CI: 1.03–4.39, P<0.05); anal sex practice with last clients (43.40% versus 11.50%) (aOR 4.31: 95% CI:2.28–8.33, P<0.001); irregular condom use in past week (33.50% versus 3.00%) (aOR 5.49: 95% CI:1.89–15.98, P<0.001); alcohol consumption before sex (34.70% versus 7.80%) (aOR 2.69: 95% CI:1.22–4.96, P<0.05); past history of STIs (41.00% versus 10.80%) (aOR 2.46: 95% CI:1.22–4.97, P<0.05) and bacterial vaginosis (29.80% versus 4.29%) (aOR 6.36: 95% CI: 2.30–17.72, P<0.001). CONCLUSION: Our observations highlight the high level of vulnerability for HIV acquisition of both poor professional “kata” and nonprofessional “street vendor” FSW categories. These categories should be particularly taken into account when designing specific prevention programs for STIs/HIV control purposes.